Analysis of aerosol climate effects under global warming - Li Guo (E3S Web of Conferences)
Global warming is a global environmental problem that has a profound impact on natural ecosystems, human socio-economic activities and the future fate of the planet. Aerosols, as tiny particles that are widespread in the atmosphere Its climate effects are complex and uncertain, and it is a key factor in global climate change research. This essay first introduces the definition and classification of aerosols, including natural source aerosols and anthropogenic source aerosols. Then it analyzed the interrelationship between global warming and aerosols. Then it explored the differences in aerosol impacts in various regions, using North China, Northeast China and the Qaidam Basin as examples. It was found that the differences in the spatial and temporal distribution of aerosols can be summarized from the seasonal and interannual variations of Aerosol Optical Depth (AOD) as well as the characteristics of the spatial distribution. The higher AOD values in spring and summer are mainly affected by sand and dust aerosols, localized pollution, and the EI Niño-Southern Oscillation (ENSO) phenomenon. The spatial distribution of AOD showed heterogeneity. The research provides an important scientific basis for the development of effective climate policy and response measures.